First report of collar rot caused by Pseudomonas aeruginosa on calla lily (Zantedeschia elliottiana) - SHANMUGAM, Veerubommu; THAKUR, Himankshi; PAUL, Surender; BHADWAL, Priyanka; MAHAJAN, Surbhi; KUMAR MONDAL, Kalyan (Phytopathologia Mediterranea, 2017)
Collar rot of calla lily cultivated in Himachal Pradesh, India, was recorded during 2011–2013, and the pathogen causing the disease was identified as Pseudomonas aeruginosa. The disease occurred on roots, rhizomes and stems of host plants, causing severe rotting and breakage, and was predominant during the rainy season (June-August) each year. . This is the first record of Pseudomonas aeruginosa affecting calla lily worldwide.